Peningkatan Strategi Pemasaran dan Branding Keripik Tempe Pedo - Tirtadidjaja, Kendrew; Sari, Afita; Sashadila, Anamira; Mulsoe, Rerry Farenza; Melvern, Dave; Quinn, Rachel; Thelim, Debby Emmanuela (Journal Pemberdayaan Masyarakat Indonesia, 2025)
Keripik Tempe PEDO is an MSME selling light snack products originally made from Kawahmanuk Village, Darma District, Kuningan Regency, West Java. So far, Keripik Tempe PEDO only has one product, tempe chips. The UMKM was once inactive and became one of the reasons it became a part of the 2024 Community Development program to revive the business. After carrying out direct mentoring activities, the problems encountered were the production process and also the very narrow sales channels. Through the 2024 Community Development activities, it is hoped that it can increase the knowledge and skills of the business owners regarding entrepreneurship, management, and the adoption of technology to develop their UMKM. The purpose of this activity is to explore and observe the processes and business potentials that can be developed. The results of this activity show that Keripik Tempe PEDO can still be developed by expanding online sales channels